ADVANCED THERAPY IN PATIENTS WITH PRIMARY AND POSTPOLYCYTHEMIC MYELOFIBROSIS - A. N. Alekseeva; O. E. Ochirova; L. B. Sodnomova; E. B. Zhalsanova (Acta Biomedica Scientifica, 2017)
Ph-negative myeloproliferative neoplasm are the group of hematologic disorders which includes primary myelofibrosis, polycythemia vera, essential trombocytemia and several rare diseases. After the discovery of V617 Fgain-of-function mutation the new period of diagnostics, treatment and evaluating of MPN prognosis began. At the current moment several molecules inhibiting JAK2 function are developed. Advanced therapy in patients with primary and post-polycythemic myelofibrosis included molecules inhibiting JAK2 function resulted in rapid and durable improvements in splenomegaly and disease-related symptoms in the phase 3 trials COMFORT-I and COMFORT-II. The effectiveness of the advanced therapy included molecule inhibiting JAK2 was evaluated in three patients with primary myelofibrosis and post-polycitemic myelofibrosis. All represented clinical cases demonstrated positive dynamics of the disease manifested in spleen size reduction, improvement of the symptoms and in one case in reduction of blood transfusions. None of three patients met serious adverse events leading to dose reduction or discontinuation of the molecule inhibiting JAK2. Target agents therapy demonstrated high treatment rates in patients with primary and post-polycythemic myelofibrosis. Thus, it is clearly necessary to perform molecular diagnosis, screening tests at early stages of the chronic myeloproliferative disease for the selection of patients in need for specific treatment.